2009
DOI: 10.1080/10286020903302315
|View full text |Cite
|
Sign up to set email alerts
|

Macagigantin, a farnesylated flavonol from Macaranga gigantea

Abstract: A new farnesylated flavonol derivative, macagigantin (1), together with two known flavonoids, glyasperin A (2) and apigenin (3), had been isolated from the acetone extract of the leaves of Macaranga gigantea. The structure of the new compound was elucidated as 6-farnesylkaempferol based on its spectroscopic data, including UV, IR, 1D and 2D NMR, and HR-EI-MS spectra. Compounds 1-3 were evaluated for their cytotoxic properties against P-388 cells, their IC(50) values being 11.3, 6.0, and 5.1 microM, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…results indicated that compounds 46 to 48 exhibited an IC 50 values of 11.3 ± 0.4, 6.0 ± 0.9, and 5.1 ± 0.7 µM, respectively (Tanjung et al, 2009). Artonin E, which was used as a positive control, showed the IC 50 value of 1.38 ± 0.2.…”
Section: Anticancer Activitymentioning
confidence: 93%
See 2 more Smart Citations
“…results indicated that compounds 46 to 48 exhibited an IC 50 values of 11.3 ± 0.4, 6.0 ± 0.9, and 5.1 ± 0.7 µM, respectively (Tanjung et al, 2009). Artonin E, which was used as a positive control, showed the IC 50 value of 1.38 ± 0.2.…”
Section: Anticancer Activitymentioning
confidence: 93%
“…Bioassay-guided isolation from the methanol extract of the leaves led to the isolation of two cytotoxic flavonoids named macarhizinoidins A (55) and B (56). On cytotoxic evaluation against murine leukemia P-388 cell lines, compounds 55 and 56 indicated the IC 50 values of 11.4 and 13.9 µM, respectively (Tanjung et al, 2010).…”
Section: Anticancer Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of dihydroflavonol and flavone derivatives in the genus Macaranga is very limited. To our knowledge the dihydroflavonol derivatives have been isolated and identified only in three species, M. alnifolia [1], M. conifera [10], and M. pruinosa [6], while the presence of the flavone is the second time after a similar compound has been isolated from M. gigantea [7]. Thus, the presence of these flavonoids could have a significant as a marker of a certain group of Macaranga.…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemical investigation has revealed that this genus is a rich source of phenolic compounds, particularly the isoprenylated and geranylated flavonoids and stilbenes [1,3]. In the course of our phytochemical study on Indonesian Macaranga, recently we reported the isolation of isoprenylated flavanones and dihydrochalcones from M. trichocarpa [4], isoprenylated, geranylated and farnesylated flavonols from M. rhizinoides [5], M. pruinosa [6], and M. gigantea [7], respectively, and a unique stilbene and dihydroflavonol derivatives containing an irregular sesquiterpenyl side chain from M. pruinosa [6]. As part of this study, we have also examined a species collected from Kalimantan island of Indonesia, M. lowii King ex.…”
Section: Introductionmentioning
confidence: 99%